Assessment of knowledge attitude and preventive behavior of pulmonary tuberculosis among Myanmar refugees in Ban Mai Nai Soi temporary shelter Mae Hong Son Thailand - Sittipong Sreechat (Chulalongkorn University, 2014)
Thesis (M.P.H.)--Chulalongkorn University, 2012